The role of pH in the separation of Lu and Yb by ion-exchange explained by novel chemical structures of lanthanide complexes - Cynthia Cáceres-Rivero; Bertha Juli Ramos-Trujillo; Yadberto Farfán; Jose Luis Solis; Patricia Bedregal (Results in Chemistry, 2022)
The individual separation of lanthanides is very complex due to the similarities between these elements. Ion-exchange separations with carboxylic acids are widely studied, but the importance of pH is overlooked. This study used citric acid to evaluate Lu and Yb separation with Dowex 50W-X8. The separation was monitored by X-ray fluorescence. Five new structures of Lu and Yb citrates are proposed. Better separation occurs when the pH of the ligand is pH 4.5, where a mononuclear structure is formed. Conversely, polynuclear structures are formed at higher pH, and separation fails. X-ray diffraction reveals different phases at each pH value, and FTIR results support the proposed structures.